2023
DOI: 10.1039/d2fo03213a
|View full text |Cite
|
Sign up to set email alerts
|

Association between pre-diagnostic dietary antioxidant vitamin consumption and ovarian cancer survival: a prospective cohort study

Abstract: Pre-diagnostic higher vitamin C and β-carotene intake was associated with improved ovarian cancer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…In our previous study, we found that intake of high-quality macronutrients, purine, and dietary antioxidant vitamins (including vitamin C and β-carotene) before diagnosis was associated with improved survival among females with OC. 29,45,56 Meanwhile, our previous study also explored the association between pre-diagnosis dietary patterns and OC survival as dietary patterns included the diet as a whole. We found that pre-diagnosis adherence to healthy pattern (loaded high in fruit, egg, vegetable, legumes and legume products, whole grain, fish, and tubers) was associated with better OS in OC patients, and adherence to animal pattern (loaded high in animal organs, animal blood and processed meat products) was the exact opposite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we found that intake of high-quality macronutrients, purine, and dietary antioxidant vitamins (including vitamin C and β-carotene) before diagnosis was associated with improved survival among females with OC. 29,45,56 Meanwhile, our previous study also explored the association between pre-diagnosis dietary patterns and OC survival as dietary patterns included the diet as a whole. We found that pre-diagnosis adherence to healthy pattern (loaded high in fruit, egg, vegetable, legumes and legume products, whole grain, fish, and tubers) was associated with better OS in OC patients, and adherence to animal pattern (loaded high in animal organs, animal blood and processed meat products) was the exact opposite.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of green and red/purple FV were aligned with findings that a high intake of dietary antioxidant vitamins before diagnosis is associated with improved survival in our previous study. 45 The inverse associations of total, green, and red/purple FV intake on OC mortality are biologically plausible. Green FV contains iron, vitamin K, vitamin C, beta-carotene, lutein, sulforaphane, and others.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Another case-control study using an FFQ in 254 patients and 652 controls to measure ascorbate consumption in the five years before the diagnosis of ovarian cancer also revealed that ascorbate reduced the risk of ovarian cancer in the group with the highest ascorbate consumption (>140.25 mg/day) compared with the group having the lowest consumption (<66.50 mg/day) (OR = 0.31) [87]. Furthermore, a hospitalbased prospective cohort study of ovarian cancer patients aged 18 to 79 between 2015 and 2020 found that higher ascorbate dietary intake (one year before diagnosis) based on a 111-item self-administered FFQ was associated with improved ovarian cancer survival after a median of 37.19 months of follow-up (hazard ratio (HR) = 0.43) [88]. However, another FFQ-based prospective cohort study followed 97,275 females in the California Teachers Study cohort for eight years and found higher dietary ascorbate intake (>665 mg/day) could significantly increase the risk of ovarian cancer by 150% compared to the group with the lowest ascorbate intake (≤75 mg/day) [89].…”
Section: The Effect Of Ascorbate In the Prevention Of Ovarian Cancermentioning
confidence: 99%